2012
DOI: 10.1007/s00404-012-2248-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to insomnia and sleepiness in the late third trimester of pregnancy

Abstract: Insomnia and sleepiness were prevalent in the late third trimester of pregnancy in which lifestyle factors and maternal and neonatal body composition were significant predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 29 publications
1
48
1
1
Order By: Relevance
“…During the third trimester, sleep disturbance and sleepiness usually increase due to sleep disorders (i.e. restless legs, sleep-related breathing disorders) and/or leg cramps and fetal activity [6]. The nocturnal sleep and daytime sleepiness symptoms in narcolepsy women have not been characterized during pregnancy but they appear to follow the pattern seen in healthy women with higher variability [1].…”
Section: Discussionmentioning
confidence: 97%
“…During the third trimester, sleep disturbance and sleepiness usually increase due to sleep disorders (i.e. restless legs, sleep-related breathing disorders) and/or leg cramps and fetal activity [6]. The nocturnal sleep and daytime sleepiness symptoms in narcolepsy women have not been characterized during pregnancy but they appear to follow the pattern seen in healthy women with higher variability [1].…”
Section: Discussionmentioning
confidence: 97%
“…These findings support previous evidence that pregnancy confers increased risk for the development of symptoms of insomnia that are analogous to a case-definition of insomnia. 18,19,43 The utility of this tool in pregnancy may be to identify those with the most severe sleep problems that persist. This may be clinically relevant given the emerging evidence that sleep disturbance increases risk for adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…41 Several studies of pregnant women report high rates of insomnia symptoms. Swanson et al 42 reported that 45% of pregnant women scored above the threshold value, and Fernandez-Alonso et al 43 identified more than 73% in late pregnancy. Manber and colleagues, 44 however, reported that only 17% of Latina women, across all trimesters, met criteria for insomnia (≥ 10) and that there was no difference across trimesters.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…Presently, the majority of published reports on sleep disturbances and/or symptoms of insomnia are from women in late pregnancy in which the rates are reported to reach upwards of > 60%. 26,46,47 Moreover, these reports do not clinically identify insomnia, only the presence of symptoms. For example, Fernandez-Alonso and colleagues used the Insomnia Severity Index to ascertain …”
Section: Sleep Deficiency In Early Gestationmentioning
confidence: 99%
“…46 While this is a commonly used instrument, the focus is on severity rather than a case definition of insomnia. Also, since a majority of women indicate experiencing symptoms of insomnia at least once in the last month, 40,48 it may not be very sensitive or specific in identifying primary insomnia in pregnant women.…”
Section: Okun Et Almentioning
confidence: 99%